Faktor Yang Mempengaruhi Penerapan Konservatisme Dalam Akuntansi Perusahaan Manufaktur Di Sektor Aneka Industri - Yusri, Rahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aims to determine the analysis of factors that influence the application of conservatism in accounting in manufacturing companies in various industrial sectors in theIndonesian ShariaStock Index for the2018-2022 period. The research method used in this research is a qualitative method. The data analysis used in this research is Descriptive Statistics, Inferential Analysis, Model Testing. The results of this research show that the Prob value of the Intentional Capital (IM) variable is 0.6203, namely ≥ 0.05, so the Intentional Capital (IM) variable is not significant for the Accounting Conservatism variable, at a significance level of 5%. It isknown that the Prob value ofthe Debt Convernantvariable is 0.2971, namely ≥ 0.05, so the Debt ConvenantC variable is not significant for the Accounting Conservatism variable, at a significance level of 5%. It isknown that theProb value ofthe Financial Distressvariable is 0.0435, namely ≤0.05, so the FD variable is significant to the KA variable, at a significance level of 5%. Keyword: Capital Intensity, Debt Covenants,Financial Distress, Accounting Conservatism